Catch composition, catch rates and size selectivity of three long-line methods in the Algarve (southern Portugal) - Erzini, Karim; Gonçalves, J. M. S.; Bentes, L.; Lino, P. J.; Ribeiro, J. (Ministerio de Agricultura, Pesca y Alimentacion, 1999)
Three long-line methods have been studied in the Algarve: 1) small-hook long-line for inshore (less than 30 m) ‘white’ sea breams (Sparidae); 2) small-hook long-line for deeper water (40-60 m) ‘red’ sea breams; and 3) deep water (500-700 m) semi-pelagic long-line for hake Merluccius merluccius (Linnaeus, 1758). Selectivity studies were carried out with three hook sizes in the first two cases: Mustad round-bent Quality 2369 hooks, numbers 15, 13, and 11, baited with a standardsized razor-shell Ensis siliqua (Linnaeus, 1758). Four hook sizes (numbers 10, 9, 7, and 5) of Stell round-bent, eyed hooks were used in the semi-pelagic long-line selectivity study, baited with a half of a standard-sized sardine. Some factors affecting catch composition and catch rates of the small hook long-lines were also evaluated: bait, gangion length, setting time, fishing ground, and depth. Species diversity was relatively high, with 40, 36 and 27 species, respectively, in the three studies. However, the catches were dominated by a limited number of species. Catch rates (number of fish per 100 hooks) were variable (< 5 %; > 20 %), with a general decrease in catch rate with increasing hook size in all the studies. In general, the catch size distributions for the different hook sizes for each species were highly overlapping, with little or no evidence of differences in size selectivity. Hooks caught a wide size-range for each species, with few or no illegal-sized fish, in most cases. Some implications of these results for the management of multi-species, multi-gear fisheries are discussed. info:eu-repo/semantics/publishedVersion